Amelioration of Nicotine-Induced Osteoarthritis by Platelet-Derived Biomaterials Through Modulating IGF-1/AKT/IRS-1 Signaling Axis. (4th August 2020) - Lo, Wen-Cheng; Dubey, Navneet Kumar; Tsai, Feng-Chou; Lu, Jui-Hua; Peng, Bou-Yue; Chiang, Pao-Chang; Singh, Abhinay Kumar; Wu, Chia-Yu; Cheng, Hsin-Chung; Deng, Win-Ping
Besides inhalation, a few studies have indicated that the uptake of nicotine through air or clothing may be a significant pathway of its exposure among passive smokers. Nicotine is well known to exert various physiological impacts, including stimulating sympathetic nervous system, causing vascular disturbances, and inducing cell death. Therefore, we aimed to establish whether exposure of nicotine could induce articular cartilage degeneration in a mouse model of osteoarthritis (OA). We specifically assessed dose-dependent effect of nicotine in vitro to mimic its accumulation. Further, during the in vivo studies, mice subcutaneously administered with nicotine was examined for OA-associated pathologic changes. We found that nicotine significantly suppressed chondrocytes and chondrogenic markers (Sox, Col II, and aggrecan). Nicotine-treated mice also showed altered knee joint ultrastructure with reduced Col II and proteoglycans. After corroborating nicotine-induced OA characteristics, we treated this pathologic condition through employing platelet-derived biomaterial (PDB)-based regenerative therapy. The PDB significantly suppressed OA-like pathophysiological characteristics by 4 weeks. The mechanistic insight underlying this therapy demonstrated that PDB significantly restored levels of insulin-like growth factor 1 (IGF-1) signaling pathway proteins, especially pIGF-1 R, pAKT, and IRS-1, regulating extracellular matrix synthesis by chondrocytes. Taken together, the PDB exerts regenerative and reparative activities in nicotine-mediated initiation and progression of OA, through modulating IGF-1/AKT/IRS-1 signaling axis.